PERANCANGAN DAN ANALISA SISTEM KENDALI FREKUENSI SISTEM TENAGA LISTRIK DENGAN METODE PENEMPATAN KUTUB - Heru Dibyo Laksono; Aditya Putra Pratama (Jurnal Teknologi Informasi dan Pendidikan, 2017)
This study discusses the application of Polar Placement method using Bass - Gura algorithm on Non - Reheat type frequency electric control system with emphasis on frequency deviation on power system. The performance indicators of electric power system that can be calculated and observed include error analysis, response speed, response quality, frequency domain analysis, stability analysis and robustness analysis of the frequency deviation response of electric power system. The simulation results show that the non-reheat type deviation of electric power with Polar Placement method shows better result compared to non-reheat type frequency power deviation response without the Polar Placement method with a steady state error value of 0.0041, the rise time value of 0.0562 second, the peak time value is 0.0049 seconds, the time value of the steady state is 0.5113 seconds, the maximum pass value is 19.2112%, the root of the characteristic equation which all the parts are negative, the maximum peak value is 1.0049 and the maximum peak value of complementary sensitivity is 0.0051. Keywords: Frequency Deviation, Polar Placement, Bass - Gura Algorithm, Non – Reheat